Interaction of topology and algebra in arithmetic geometry - Camara, Alberto (2013)
This thesis studies topological and algebraic aspects of higher dimensional local fields and relations to other neighbouring research areas such as nonarchimedean functional analysis and higher dimensional arithmetic geometry.